A long-term follow-up of patients with prolonged asystole of greater than 15 s on head-up tilt testing. (15th January 2016) - Sau, Arunashis; Mereu, Roberto; Taraborrelli, Patricia; Dhutia, Niti M.; Willson, Keith; Hayat, Sajad A.; Francis, Darrel P.; Sutton, Richard; Lim, Phang Boon
Abstract: Background: Head-up tilt (HUT) is used for diagnosis of vasovagal syncope (VVS), and can provoke cardioinhibition. VVS is usually considered benign, however pacemaker insertion may be indicated in some patients. We sought to characterize the long-term outcomes of patients with prolonged asystole (> 15 s) on HUT. Methods: We conducted a retrospective study on patients with asystole > 15 s on HUT identified from 5133 patients who were investigated between 1998 and 2012 at our institution. Patients were mailed questionnaires or telephoned to ascertain outcomes. Where contact was not possible, the patients' general practitioners were contacted to request up-to-date information. Results: A total of 26 patients with a mean age of 45 ± 18 years and a mean duration of asystole on HUT of 26 ± 7 s were successfully followed up from a total of 77 patients identified. The follow-up duration was 99 ± 39 months. Six patients had undergone pacemaker (PPM) implantation. Of the patients without PPM, 16 reported spontaneously improved symptoms. Ten patients sustained injury prior to HUT compared with one after HUT, when a clear diagnosis was made and management advice was given. There were no major injuries or deaths after HUT. The 6 patients with PPMs had a mean age of 60 ± 16 (67% male) at HUT. Four patients had no further syncope after PPM and two demonstrated improvement but still experienced recurrent syncope. Conclusions: Prolonged asystole (> 15 s) on tilt does not necessarily predict adverse outcomes with most patients improving spontaneously over the long-term. Pacemaker insertion in selected patients may reduce syncope recurrence but does not always abolish it.